Serotonin and Effort-Based Decision-Making: Dissociating Behavioral Effects of 8-OH-DPAT and PCPA - Kunčická, D; Cmarková, N; Ondráčková, S; Kačer, D; Rodriguez, D; Valeš, K; Svoboda, J; Brožka, H; Stuchlík, A (Physiological research, 2024)
Effort-based decision-making is particularly relevant to psychiatric conditions where motivation deficits are prominent features. Despite its clinical significance, the neurochemical mechanisms of this cognitive process remain unclarified. This study explores the impact of serotonin synthesis inhibition (PCPA) and modulation of serotonin release and 5-HT1A receptor agonism (8-OH-DPAT) on effort-based decision-making in rats. Adult male rats were trained in a modified T-maze task where they could obtain a high reward for climbing a mesh barrier or a low reward for no extra effort. Following training, rats received either acute 8-OH-DPAT treatment or subchronic PCPA treatment and were tested on their choices between high- and low-effort arms. The goal-arm choices and goal-arm entrance latencies were recorded. Next, homovanillic acid and 5-hydroxyindoleacetic acid, metabolites of dopamine and serotonin, respectively, were quantified in the rats' prefrontal cortex, striatum, and hippocampus. 8-OH-DPAT significantly increased low-effort, low-reward choices and increased goal-arm latency. In contrast, PCPA treatment did not affect these measures. Both PCPA and 8-OH-DPAT significantly decreased 5-hydroxyindoleacetic acid levels in the prefrontal cortex and the hippocampus. 8-OH-DPAT treatment was also associated with decreased homovanillic acid levels in the hippocampus. Our findings suggest that the overall reduction of serotonin levels alone does not affect effort-based decision-making and highlights the possible role of the hippocampus and the 5-HT1A receptor in this cognitive process.
Keywords: Behavior, Animal; serotonin; odměna; Rats; Male; potkani Sprague-Dawley; Serotonin; mužské pohlaví; Maze Learning; Reward; krysa rodu Rattus; rozhodování; 8-hydroxy-2-(di-N-propylamino)tetralin; Decision Making; Serotonin 5-HT1 Receptor Agonists; agonisté serotoninového receptoru 5-HT1; zvířata; chování zvířat; Rats, Sprague-Dawley; bludiště - učení; 8-Hydroxy-2-(di-n-propylamino)tetralin; Animals